Modification Of The Model Problem Solving Learning With The Approach Of Offline in Class X Private SMK az zahra sonomartani - Ade Irwansyah Nasution; Rohani; Dwi Wulan Tristiana (CV. AFDIFAL MAJU BERKAH, 2021)
This study aims to determine the improvement of learning outcomes of biology students through the Modification of the Model Problem Solving Learning Approach With Offline in class X SMK Swasta Az Zahra Sonomartani. Types of quantitative research through the method of Non-equialent Control Group Design. The population used in this study 1 class i.e. class X Computer Engineering and Networks that learned by a Modification of the Model Problem Solving Learning Approach Offline. Data collection in this study using the test, as well as the technique of data analysis used t-Test. The results of the test shows the average value of the pretest of the 34 students in the class that learned Modification of the Model Problem Solving Learning Approach with Offline namely 46,24 with a standard deviation of 7,897 and on the class that learned Modification of the Model Problem Solving Learning approach with Offline of 34 students from the average value of posttest of 73,56 with a standard deviation of 3,230. Berdasrakan the results of hypothesis testing using independent t-test was calculated using IBM SPSS Stastics Version 20 for windows was obtained tcount > ttable that is (2,833 > 1,671) so it can be concluded that there is an increase in learning outcomes of biology by using a modification of the model Problem Solving learning approach with offline in class X SMK Swasta Az Zahra Sonomartani.